Laser Ignition of an IC Engine Using an Nd: YAG Laser - Zeenath Fathima, S.; Maria Antoine Pushparaj, C.; Shiva Shankare Gowda, A. S. (Asian Review of Mechanical Engineering, 2012)
The use of laser energy to ignite gas and liquid based fuel-air mixtures has been the subject of a number of studies and laboratory experiments at a fundamental level over the past 30 years. The practical implementation of this laser application has still to be fully realized in a commercial automotive application. Laser Ignition (LI), as a replacement for Spark Ignition (SI) in the Internal Combustion (IC) engines of automotive vehicles, offers several potential advantages including extending lean burn capability, reducing the cyclic variants between combustion cycles and reducing the overall ignition package costs, weight and energy requirements. This paper reports on the current research being undertaken which examines the effects of engine combustion performance and stability when specific laser parameters (beam energy, minimum spot size and focal length/volume) are varied. A Q-switched Nd: YAG laser operating at the fundamental wavelength 1064 nm was used to ignite gasoline and air mixtures.